The importance of focus on form in communicative language teaching - Ellis, Rod (2015)
Long (1991) distinguished two approaches to language teaching, which he called ‘focus-on-forms’ and ‘focus-on-form’. In this article I discuss ‘focus-on-form’ from both a theoretical perspective by outlining the psycholinguistic rationale for this type of instruction and from a practical perspective by identifying the strategies that students and teachers can use when doing focus-on-form. I conclude by emphasizing the importance of including a focus-on-form in communicative language teaching in order to facilitate incidental language learning and thus reject the commonly held view that teachers should not ‘interfere’ when students are performing a communicative task. I also suggest that ‘focus-on-forms’ and ‘focus-on-form’ should be seen as complementary rather than oppositional approaches to teaching.